The way forward for assessing the human health safety of cosmetics in the EU - Workshop proceedings. (30th April 2020) - Rogiers, Vera; Benfenati, Emilio; Bernauer, Ulrike; Bodin, Laurent; Carmichael, Paul; Chaudhry, Qasim; Coenraads, Pieter Jan; Cronin, Mark T.D.; Dent, Matthew; Dusinska, Maria; Ellison, Corie; Ezendam, Janine; et al.
Highlights: In the EU only animal-free methods may be used for safety assessment of cosmetics. Next Generation Risk Assessment (NGRA) offers a suitable framework for safety assessment. NGRA makes use of animal-free New Approach Methodologies (NAMs). NAMs consist of in chemico, in silico, in vitro and ex vivo methods. Abstract: Although the need for non-animal alternatives has been well recognised for the human health hazard assessment of chemicals in general, it has become especially pressing for cosmetic ingredients due to the full implementation of testing and marketing bans on animal testing under the European Cosmetics Regulation. This means that for the safety assessment of cosmetics, the necessary safety data for both the ingredients and the finished product can be drawn from validated (or scientifically-valid), so-called "Replacement methods". In view of the challenges for safety assessment without recourse to animal test data, the Methodology Working Group of the Scientific Committee on Consumer Safety organised a workshop in February 2019 to discuss the key issues in regard to the use of animal-free alternative methods for the safety evaluation of cosmetic ingredients. This perspective article summarises the outcomes of this workshop and reflects on the state-of-the-art and possible way forward for the safety assessment of cosmetic ingredients for which no experimental animal data exist. The use and optimisation of "New Approach Methodology" that could be useful tools in the context of the "Next Generation Risk Assessment" and the strategic framework for safety assessment of cosmetics were discussed in depth.